The utilization of mackarel tuna as Nutrient-Dense Complementary Food (MPASI) - Tanjung, Tiara Nanda Puspita; Eliska, Eliska; Tanjung, Nadya Ulfa (Institute of Computer Science (IOCS), 2024)
This study explores the potential of mackerel tuna as a nutritious complementary food source (MPASI) due to its rich protein content and high availability, which could play a crucial role in a balanced diet for toddlers. The aim of this research is to investigate the potential of mackerel tuna as a protein source in nutritious complementary foods for breastfeeding infants. This study employs experimental and observational methods to evaluate the potential of mackerel tuna as a complementary food. The results are analyzed descriptively, and protein content analysis is conducted on mackerel tuna nuggets. The research is carried out in three stages: recipe creation, recipe modification trials, and protein content testing. Protein content analysis, conducted at the Biochemistry Laboratory of FMIPA, Universitas Sumatera Utara, using spectrophotometry on mackerel tuna nugget samples, showed a protein content of 0.35 grams per gram, indicating 35 grams of protein in 100 grams of nuggets. Processed mackerel tuna in the form of nuggets represents a promising variation of MPASI menu rich in protein content. Protein is crucial for supporting the growth and development of toddlers as it is a primary nutrient essential for physical growth, including bone and muscle development. Additionally, protein plays a role in brain development, enhancing cognitive function in toddlers.